Balad el-Ziblé (Country of Rubbish): Moral Geographies of Waste in Post-revolutionary Tunisia. Issue 1 (2nd January 2018) - Darwish, Siad
ABSTRACT: Waste sullies, physically and morally, polluting people and places, and defining or altering their position within social and spatial hierarchies. Given this polluting quality and the moral charge of the idiom of pollution, waste and its distribution are indicative of how places are imbued with moral judgment and at the same time waste illustrates how places themselves can become morally polluting. In the context of a waste crisis that followed the Tunisian Revolution of 2011, it is argued here that an attention to waste as material and symbolic category demonstrates the recursive relationship between materials, people, their thoughts and actions, in the moralisation of place. Examining this waste crisis in terms of a Tunisian moral geography of waste, which was established under colonialism and labels certain people and places as clean and dirty, reveals the dynamic and historically contingent nature of moral spaces and depicts them as sites for socio-spatial struggles that in themselves illuminate the revolution in novel ways. Finally, it is concluded that the polluting quality of waste spilled over the boundaries of Tunisia's moral geography to morally sully the whole time period and political process of Tunisia's transition.